Students' Perception Of Using ChatGPT At English Education Departement Of STAI Hubbulwathan Duri - Yoni Alwi (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
This study aimed to describe the perceptions of students in the English Education Program toward ChatGPT at Sekolah Tinggi Agama Islam (STAI) Hubbulwathan Duri. The research adopted the Technology Acceptance Model (TAM) approach with a quantitative method. Data was collected through a closed-ended questionnaire completed by 22 students. The questionnaire utilized a Likert scale to assess students’ perceptions of the ease of use (PEOU) and perceived usefulness (PU) of ChatGPT in learning. The research found that students have positive perceptions of ChatGPT, particularly in enhancing learning effectiveness, time efficiency, and information accessibility. However, challenges such as dependence on technology and the occasional irrelevance of information quality were also identified. Data analysis was conducted by converting questionnaire scores into percentages to illustrate the levels of acceptance and satisfaction among students toward ChatGPT. This study was expected to provide insights for educational institutions and technology developers regarding the optimal integration of ChatGPT in learning. The findings also highlight the importance of a balanced approach to utilizing technology to support effective and innovative learning.